Robust Decision-Making in the Water Sector A Strategy for Implementing Lima's Long-Term Water Resources Master Plan - Kalra, Nidhi (World Bank E-Library Archive, 2015)
00 million) in investment costs. Second, the study helped focus future efforts on demand-side management, pricing, and soft infrastructure, a refocusing that is difficult to achieve in traditional utility companies. Third, the study helped SEDAPAL gain the support of regulatory and budget agencies through the careful analysis of alternatives. Fourth, the study allowed the utility to postpone lower priority investments, and to analyze future options based on climate and demand information that simply is not available now